The Death of Jane Eyre:A Pioneer Woman Who Returned to Tradition (Journal of humanities and social sciences exploratio, 2025)
Jane·Eyre, the representative work by Charlotte Bronte, portrays the protagonist's journey from familial dependence to independence. The first half of the novel depicts Jane's resilient character as she courageously resists discrimination and abuse, while the second half explores her struggles and choices in love. Although ultimately conforming to male dominance and assuming the role of an ordinary housewife, Jane's trajectory still reflects the constraints faced by British women during that era. While feminist ideas are present in Jane Eyre, compromises were made that prevented complete rebellion against patriarchal societal norms.
Keywords: Jane·Eyre; Charlotte·Bronte; Self-contradiction; Adult fairy tale